Hydatid Cyst Disease of the Spine: Evaluation of Seven Cases - Ferit KUŞCU; Bedia MUTAY SUNTUR; Güner MENEKŞE; Tuncay ATEŞ; Ali İhsan ÖKTEN; Aslan GÜZEL (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2013)
Introduction: Hydatid cyst is a zoonotic infectious disease, and generally affects the liver and lungs. Spinal involvement is a very rare condition. In this study, we aimed to evaluate patients with spinal hydatid disease. Materials and Methods: Seven patients with spinal hydatid disease treated between 2009 and 2012 were evaluated retrospectively. Demographic characteristics, symptoms and findings, spinal involvement levels, and treatment modalities of the patients were recorded. Results: Four (57%) of the patients were male and 3 (43%) were female. The mean age of the patients was 43 ± 18.2 years. Four (57%) cysts were in the thoracic region, 2 (29%) in the sacral region and 1 (14%) in the lumbar region. Cysts were secondary to spread from other organ systems in four patients due, and were primary in three patients. Conclusion: Hydatid cyst is an infectious disease that may affect various organs. Patients with hydatid cyst in the liver or lung should be checked carefully regarding other system involvement, including the spinal region.